Characterization of swine-origin H1N1 canine influenza viruses. Issue 1 (1st January 2019) - Wang, Guojun; dos Anjos Borges, Luiz Gustavo; Stadlbauer, Daniel; Ramos, Irene; Bermúdez González, Maria C.; He, Jianqiao; Ding, Yangbao; Wei, Zuzhang; Ouyang, Kang; Huang, Weijian; Simon, Viviana; Fernandez-Sesma, Ana; et al.
ABSTRACT: Host switch events of influenza A viruses (IAVs) continuously pose a zoonotic threat to humans. In 2013, swine-origin H1N1 IAVs emerged in dogs soon after they were detected in swine in the Guangxi province of China. This host switch was followed by multiple reassortment events between these H1N1 and previously circulating H3N2 canine IAVs (IAVs-C) in dogs. To evaluate the phenotype of these newly identified viruses, we characterized three swine-origin H1N1 IAVs-C and one reassortant H1N1 IAV-C. We found that H1N1 IAVs-C predominantly bound to human-type receptors, efficiently transmitted via direct contact in guinea pigs and replicated in human lung cells. Moreover, the swine-origin H1N1 IAVs-C were lethal in mice and were transmissible by respiratory droplets in guinea pigs. Importantly, sporadic human infections with these viruses have been detected, and preexisting immunity in humans might not be sufficient to prevent infections with these new viruses. Our results show the potential of H1N1 IAVs-C to infect and transmit in humans, suggesting that these viruses should be closely monitored in the future.